ANALYSIS OF EMPLOYEE SATISFACTION TO IMPROVE THE QUALITY OF WORK AT BHAYANGKARA HOSPITAL TK II SARTIKA ASIH - Rahman, Adam Abdul (CV. AFDIFAL MAJU BERKAH, 2023)
This study aims to determine the analysis of job satisfaction in order to improve the quality of work at BhayangkaraTK II Hospital Sartika Asih Bandung. The research method used is qualitative with a descriptive approach. Data collection techniques used are field observations, literature studies, interviews and questionnaires. The sampling technique used purposive sampling technique with the number of respondents as many as 2 hospital employees. From the research results, it was found that job satisfaction analysis was quite effective on the quality of employee work. However, there are a few problems that arise, including: 1) Supporting facilities that are felt to be dissatisfied will hinder employees in their work and reduce job performance (work results in terms of quality and quantity) will decrease and it could be that an employee cannot carry out their duties in accordance with their responsibilities. the answer given to him. 2) Lack of appreciation for work, where appreciation is very important because it can provide enthusiasm and motivation which can produce quality and accomplished workers. The author provides suggestions for these problems, namely: 1) It is better if the Byangkara Hospital tk II sartika asih Bandung strives to create a database of the number and condition of supporting items such as computers and printers in each room and make submissions to the renmin/ICT subsection if the condition of these items badly damaged, but if the item is still possible it can be used and repaired, you can submit it to the ICT department, 2) As an important part of the institution, employees at BhayangkaraTK II Sartika Asih Bandung Hospital must be able to develop a professional attitude and mentality and know the risks of work so that maintaining work safety. So that the positive image of the hospital towards the environment is formed by itself.